Productivity subarea of CBM field and its key controlling factors: A case study in the Hancheng pilot test area, southeastern Ordos Basin, China. Issue 1 (January 2019) - Liu, Yanfei; Tang, Dazhen; Li, Song; Xu, Hao; Tao, Shu; Zhao, Junlong; Geng, Yunguang; Fan, Hongbo
The Hancheng block in the southeastern Ordos Basin is one of the earliest and the most important areas for coalbed methane exploration and development in China. However, there are significant production variations in different wells or even some adjacent wells in the Hancheng block. To reveal the reasons of production differences in such a small scale, further detailed studies of coalbed methane productivity in the Hancheng pilot test area, a precursor trial area in Hancheng block with mature, well-characterized coalbed methane reservoirs and long-term production database, were conducted. The influence of nine factors (including engineering and geological factors) on gas production was analyzed. By introducing the rough set theory, which is applicable to the vague, imprecise, and incomplete information system, this paper presents a method for quantitative evaluation of the influencing factors on gas production. The results indicate that there are certain distribution characteristics of productivity in Hancheng pilot test area, which can be partitioned into four zones. The degressive order of the influencing degree of these nine factors is (i) the distance between the well and the fault, (ii) the structure curvature of the coal seams, (iii) the gas content, (iv) the critical reservoir ratio, (v) the volume of the fracturing liquids per meter, (vi) the volume of the fracturing sand per meter, (vii) the dynamic liquid level drop rate, (viii) the depth, and (ix) the thickness. Geological factors, especially the influence of fault, structural curvature of the coal seams and gas content, play a major role in controlling long-term gas production. Engineering factors (effect of fracturing and dynamic liquid level drop rate) have always been integral parts of coalbed methane development.